The Role of Entrepreneurial Mental Innovation and Local Wisdom on Organizational Resilience - Africano, et Al. , Fernando (International Journal of Entrepreneurship and Business Management, 2023)
Purpose: This study aims to determine the relationship between entrepreneurial mentality and local wisdom on organizational resilience with the variable innovation as a medium for this relationship. This research was conducted on Nusantara UMKM in Palembang City.Methodology/approaches: The approach to be used in this study is a quantitative research method. This study develops a path analysis model to test the hypotheses that have been developed. The population in this study were 300 entrepreneurs from UMKM Nusantara in Palembang City. The sample used in this study were 61 entrepreneurs.Findings:The results of the study show that product innovation, local wisdom and entrepreneurial mentality have a positive and significant effect on organizational resilience. Local wisdom and entrepreneurial mentality have a positive and significant effect on product innovation. Product innovation mediates the influence of entrepreneurial mentality and local wisdom on organizational resilience Novelty/value:In this study in the context of SMEs, innovation behavior is a variable that is quite important, especially in dealing with the complexity and dynamics that occur in the world of SMEs. This result also underlines that the relationship between these variables can also occur possibly because the education of the respondents is high enough so that it can help the cognitive of the respondents in making an innovation to support their businesses and in the end they are able to survive even in an uncertain environment.